2011
DOI: 10.1002/pssb.201046429
|View full text |Cite
|
Sign up to set email alerts
|

Structure and X‐ray spectrum of crystalline poly(3‐hexylthiophene) from DFT‐van der Waals calculations

Abstract: The minimum-energy geometrical structure of the regioregular head-to-tail poly(3-hexylthiophene) (rr-HT-P3HT) polymer has been addressed by means of density functional theory (DFT) calculations which include long-range (van der Waals) interactions. The problem of the P3HT structure has been debated in the literature in the last decades mainly for what concerns the arrangement of the alkyl side chains of the polymer and the type and content of the crystalline primitive cell. The main result of our calculations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
68
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 78 publications
10
68
0
1
Order By: Relevance
“…We also noticed, in all optimization calculations with different semiempirical methods, that the planes of the thiophene rings rotate up to 14 out of the initial common plane. Similar results are found in the literature for the P3HT, with more sophisticated calculations, using DFT with Periodic Boundary Contour (PBC) [33,38]. In their studies of polythiophenes and derivatives [44], S. S. Zade and M. Bendikov observed that, in the solid state, the same rotation can reach up to 36 .…”
Section: Methodssupporting
confidence: 85%
“…We also noticed, in all optimization calculations with different semiempirical methods, that the planes of the thiophene rings rotate up to 14 out of the initial common plane. Similar results are found in the literature for the P3HT, with more sophisticated calculations, using DFT with Periodic Boundary Contour (PBC) [33,38]. In their studies of polythiophenes and derivatives [44], S. S. Zade and M. Bendikov observed that, in the solid state, the same rotation can reach up to 36 .…”
Section: Methodssupporting
confidence: 85%
“…A simple comparison between the length of a fully extended all-trans hexyl chain and the (100) d-spacing (See Supporting Information) also rules out the possibility of interdigitation, in agreement with previous experimental and theoretical results. [ 31,32 ] Based on the for charge carrier mobility ( μ ) is given by Equation 1 , where μ 0 is the mobility prefactor, σ /kT is the energetic disorder parameter (width of the density of states) normalized to thermal energy, Σ is the positional disorder parameter, E is the applied electric fi eld, k is the Boltzmann constant and C is an empirical constant.…”
Section: Thermal Evolution Of the Structure Of Rr-and Rra-p3htsmentioning
confidence: 99%
“…[20,29] To determine the stable crystal structure, several groups examined first-principles density functional theory (DFT) calculations, and discussed their structural properties. [30][31][32][33][34][35] However, most of these studies have been carried out using tentative orthorhombic lattices. The possibility that the material shows space groups with lower symmetry and its optical properties have not yet been theoretically discussed.…”
mentioning
confidence: 99%